A fast, non-iterative ray-intersection approach for three-dimensional microscale particle tracking. Issue 5 (2nd February 2022) - Hong, Liu; Chamorro, Leonardo P.
Abstract : We propose a non-iterative, fast, robust ray tracing method with a post-capture microlens array sensor to reconstruct sparse particle concentration. Abstract : We propose a non-iterative ray tracing method with robust post-capture microlens array sensor alignment to reconstruct sparse particle concentration in light field particle image velocimetry and particle tracking velocimetry nearly instantaneously. Voxels traversed by various rays are stored by a kd-tree to reduce memory load and computational time. A cloud point classification algorithm is employed for particle identification and spatial reconstruction. The approach is tested with a physically-based realistic model of a light field camera. Also, an optical system is assembled in a microscope to directly obtain the 3D laminar velocity field in the fully-developed region, which exhibits good agreement with the theoretical solution.